Implementasi Kurikulum 2013 Pembelajaran MatematikaDi SMP Muhammadiyah 1 Surakarta Kelas VIITahun Ajaran 2014/2015 - Sholikin, Muhammad; , Dra. Nining Setyaningsih, M.Si (2015)
This study aimed to describe the implementation of learning mathematics, facilities and infrastructure, as well as to identify factors inhibiting and supporting factors in the implementation of Curriculum 2013 SMP Muhammamdiyah 1 Surakarta class VII. This research is a descriptive study with qualitative approach. Description of the research is done by providing an overview of infrastructure, learning tools and the implementation of mathematical learning. Data collection method used is observation, documentation, and interviews. The instrument used is the scoring sheet analysis implementation of learning, lesson plan, observation sheets and sheets of questions. The results showed that (1) the readiness of facilities and infrastructure in support of the implementation of the mathematics curriculum in 2013 included in both categories, (2) learning device in the form of lesson plan created by math teachers is in a good enough categories with a value of 72,5%, (3) Implementation mathematics curriculum based on both categories in 2013 including 85% value, (4) the factors supporting the implementation of learning mathematics that mathematics teachers have training curriculum in 2013 and the good preparedness of facilities and infrastructure, and (5) the factors inhibiting the implementation of the learning of mathematics, namely active learners when learning is low and the teacher in implemanting the mathematics learning haven't been matched with the lesson plan.